Outcomes in severe tricuspid regurgitation by CMR: when severe is too severe. (25th November 2020) - Hinojar Baydes, R; Vieitez, J.M; Gonzalez-Gomez, A; Garcia-Martin, A; Hernandez-Jimenez, S; Pascual, M; Monteagudo, J.M; Garcia De Vicente, A; Zamorano, J.L; Fernandez-Golfin, C
Abstract: Introduction: Tricuspid regurgitation (TR) is related to poor prognosis independently of the etiology. Recently a new scale classification has been proposed to better characterize the grading of more than severe TR. Massive and torrential TR seem to have worse prognosis based on recent echocardiographic studies. There is no information on how that classification would apply when TR is quantified by cardiac magnetic resonance (CMR). Purpose: To define the cut-off value of massive and torrential TR by CMR and to investigate its potential prognostic implications. Methods: Consecutive patients in stable clinical status with significant TR evaluated in the Heart Valve Clinic with a contemporaneous echo and CMR were included. TR severity was evaluated by biplane vena contracta and effective regurgitant orifice method, using EPIQ system and by TR regurgitant fraction using a 1.5 Tesla CMR Philips scanner. End-point included cardiovascular mortality, tricuspid valve surgery or heart failure. Results: A total of 56 patients were included (mean age was 72±9 years, 74% females). According to echocardiography n=43 (76%) were severe TR, n=8 (14%) were massive IT and n=5 (9%) were torrential TR. Patients with massive and torrential TR showed higher RV end-diastolic volume and lower RVEF. A TR regurgitant fraction (TRF) >50% held the best accuracy to define massive / torrential TR. During a median follow up of 2.4 years (IQR: 1.1–3.3 years) 31% of the patients reached the combined endpoint. TR regugitant fraction was predictive of worse prognosis (hazard ratio per 1%TRF=1.085 [1.024–1.150] p=0.003). Patients with a massive and torrential TR showed a significantly higher rate of events (figure). Figure shows on the left (A) spline curves displaying survival free of events for each value of TR regurgitant fraction. y-axis represents the hazard ratio regurgitation fraction (green line) and 95% confidence interval (shadow). On the right (B) Kaplan Meier curves show a significantly higher rate of events in patients with RF>50%. Conclusions: Our results confirm that patients with massive/torrential TR are populations at higher risk of cardiovascular events. New classification scheme may be included in CMR grading scales. Further research will establish who may benefit the most of intensive therapeutic treatments and intervention on the tricuspid valve. Funding Acknowledgement: Type of funding source: None